3-D fracture evolution and water migration in fractured coal under variable stresses induced by fluidized mining: In situ triaxial loading and CT imaging analysis. (November 2021) - Ju, Yang; Xi, Chaodong; Wang, Shaojie; Mao, Lingtao; Wang, Kai; Zhou, Hongwei
Abstract: To reduce environmental impacts caused by traditional coal recovery, an in situ fluidized mining method based on the earthworm-like intelligent unmanned automatic mining machine (IUAMM) has been proposed, which achieves safe, efficient, and low-carbon exploitation of coal resources. The recovery of abundant thick-seam coal as a clean energy source is important for achieving net zero carbon dioxide emissions in China before 2060. In this study, we discuss the applicability of IUAMM-based fluidized mining technology to thick-seam coal recovery, and its potential impacts on geological formations and the environment, by evaluating mining-induced stress effects on coal fracture and water migration. A promising approach combining high-resolution X-ray computed tomography and in situ triaxial loading techniques is developed to explore three-dimensional (3-D) fracture evolution and water migration in fractured coal subjected to variable geostresses induced by fluidized mining. We characterize the morphologies and connectivity of 3-D fractures at various geostress stages and quantify the effects of fracture network evolution on the water permeability of fractured coal. Simultaneous fracture growth and closure caused by stress variations is also analyzed. The results indicate that the increase in water permeability induced by the fluidized mining method is smaller than that induced by traditional mining methods. Therefore, the in situ fluidized mining method can help reduce damage to rock formations and achieve green coal recovery. Highlights: An in situ testing system combining CT and triaxial loading techniques is designed. 3D fracture network evolution and water migration are characterized. Effects of fracture growth and closure due to geostress variation are discussed. Fluidized mining is beneficial to ecological environment and green coal production.